Pengaruh Asupan Vitamin terhadap Indeks Prestasi Semester (IPS) Mahasiswa Angkatan 2019 Fakultas Kedokteran Gigi Universitas Jember - Sugiarti, Mustika; Prijatmoko, Dwi; Sulistiyani, Sulistiyani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
Students have an obligation to be able to carry out activities and achieve optimally. Vitamins are important constituents of enzymatic systems that can support student learning activities. Learning achievement at university level is implemented in the form of the Semester Achievement Index. This study aims to analyze the effect of vitamin intake on the Semester Achievement Index of students class of 2019, Faculty of Dentistry, University of Jember. The population consisted of all students from the Faculty of Dentistry, University of Jember Class of 2019. The sample size that met the criteria was 104 students. Research procedures include direction, measuring height and weight, filling out nutritional intake measurement sheets, data conversion, and data input. Data analysis used ordinal regression to determine the effect of food intake on Semester Achievement Index. The average student Semester Achievement Index (IPS) is 3.30 which is included in the Very Satisfactory category. Vitamin intake simultaneously has a significant effect on the Semester Achievement Index (IPS). Analysis of the most dominant vitamin intake to increase the Semester Achievement Index of dental students class of 2019 can be seen through the odds ratio value, vitamin B1 has an odds ratio value of 6.754, B2, 1.930, and C 1.003. Vitamin intake has a significant effect on Semester Achievement Index (IPS). Vitamin B1 has the greatest influence on Semester Achievement Index followed by vitamins B2 and C. Consuming a higher intake of vitamins B1, B2 and C has the possibility of increasing students' Semester Achievement Index.